Pengembangan Motivasi dan Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia Melalui Penerapan Model Pembelajaran Examples Non Examples - Nela Ananda Rosa; Sitti Rabiah; Nurfathana Mazhud (Phonologie : Journal of Language and Literature, 2022)
Abstract. Discussing research that aims to develop student motivation and learning outcomes with the application of non-examples learning models  class XI MIPA 5 SMA Negeri 16 Makassar. This research is in its stages using class action research. The data in this study is an observation sheet and test results with primary and secondary data sources. The data analysis technique is to use criteria and assessment rubrics. The results of the study found that there were significant positive changes related to students' interests and motivations for learning, such as activeness, curiosity, and student responsibility. Evident from the increase in the average observation sheet containing these indicators which reached 75.2 at the end of cycle II. Meanwhile, the average student learning outcome also showed an increase in prescience of 54.39 increased to 62.14 at the end of cycle I and experienced a good increase at the end of cycle II to 75.14 or 81% with the number of students reaching KKM as many as 29 out of 36 students.Keyword: Motivation to learn, learning outcomes, examples non examples